An Unusual Case of Bilateral Agenesis of the Cochlear Nerves. (30th July 2012) - Soares, Vítor Yamashiro Rocha; Ferreira, Fabrício Mendes; Coimbra, Christiane França; Sampaio, André Luiz Lopez; Oliveira, Carlos Augusto Costa Pires De
Abstract : Imaging of the cochlea and internal auditory canals are increasingly important nowadays because of the growing number of cochlear implants being performed throughout the world. We report a case of a 4-year-old boy who was born deaf and was being evaluated in our service for possible cochlear implantation. Audiometry disclosed profound bilateral deafness. The magnetic resonance imaging revealed only two nerves in each inner auditory canal: one in the anterior superior quadrant, identified as the facial nerve, and one on the posterior quadrants, representing both the superior and inferior vestibular nerves. The semicircular canals were not seen and the vestibule had dysplastic morphology. The diagnosis was bilateral agenesis of the cochlear nerves and semicircular canals.